Finite difference solution of plate bending using Wolfram Mathematica - Pisačić, Katarina (Array, 2019)
This article describes the procedure of calculating deflection of rectangular plate using a finite difference method, programmed in Wolfram Mathematica. Homogenous rectangular plate under uniform pressure is simulated for this paper. In the introduction, basic assumptions are given and the problem is defined. Chapters that follow describe basic definitions for plate bending, deflection, slope and curvature. The following boundary condition is used in this article: rectangular plate is wedged on one side and simply supported on three sides. Using finite difference method, linear equation system is given and solved in Wolfram Mathematica. System of equations is built using the mapping function and solved with solve function. Solutions are given in the graphs. Such obtained solutions are compared to the finite element method solver NastranInCad.